The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11244-018-1024-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Fe Speciation on N2O Decomposition Over Fe–ZSM-5 Catalysts

Abstract: The influence of Fe speciation on the decomposition rates of N2O over Fe–ZSM-5 catalysts prepared by Chemical Vapour Impregnation were investigated. Various weight loadings of Fe–ZSM-5 catalysts were prepared from the parent zeolite H-ZSM-5 with a Si:Al ratio of 23 or 30. The effect of Si:Al ratio and Fe weight loading was initially investigated before focussing on a single weight loading and the effects of acid washing on catalyst activity and iron speciation. UV/Vis spectroscopy, surface area analysis, XPS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The results indicated that the adsorbed N2O can be easily decomposed to N2 without activation energy. Fe-ZSM-5 catalysts were used to remove N2O from gas by Richards et al (2018). Comparison of catalysts with relatively high and low Fe loadings achieved comparable levels of N2O decomposition when propane is present.…”
Section: Recommendations For Near-zero Emissions Of N2o From Biologicmentioning
confidence: 99%
“…The results indicated that the adsorbed N2O can be easily decomposed to N2 without activation energy. Fe-ZSM-5 catalysts were used to remove N2O from gas by Richards et al (2018). Comparison of catalysts with relatively high and low Fe loadings achieved comparable levels of N2O decomposition when propane is present.…”
Section: Recommendations For Near-zero Emissions Of N2o From Biologicmentioning
confidence: 99%
“…O y clusters on the exchanged sites affects the catalytic performance [13,22]. Furthermore, it is also notable that Cosites were more active than Fe-sites due to lower activation energy barrier for the direct decomposition of N 2 O [19,24].…”
Section: +mentioning
confidence: 99%
“…3d), the two bands observed at 200-260 nm and at 260-360 nm corresponding to the typical ligand to metal charge transfer (LMCT) bands of isolated Fe 3+ species in the cationic sites [19,34] and isolated or oligomeric extraframework Fe species in zeolite channels [22], respectively. The bands at 360-460 nm (iron oxide clusters) and > 450 nm (large surface oxide species) can be associated to Fe 2 O 3 particles on zeolite surface [22]. Note that the spectrum of the Fe-ZSM-5 catalyst was characterized by a low intensity absorption edge at 550 nm reflecting low concentration of Fe oxide nanoparticles, which was not detected by XRD (< 4 nm), however observed by TPR.…”
Section: Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…All the noble metal based systems are supported catalysts, and the nature of the interactions of a noble metal with the support plays also a crucial role in their activity. [27][28][29] The main disadvantage of noble-metal catalysts is the high cost, so chemists are mostly looking for suitable catalytic materials from the second groupnon-noble-metal oxide catalytic systems 22 which include a wide range of oxide types such as bulk oxides, [30][31][32] spinels, 33,34 perovskites, hexaferrites, hydrotalcites [35][36][37][38][39][40][41] etc. The use of a support allows one to increase the specific activity of metal particles due to the enhanced dispersity, which is convincingly illustrated by examples of Fe 2 O 3 and Co 3 O 4 supported on ZrO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%